Accuracy comparison of six intraocular lens formulas using total and standard keratometry measurements with the iolmaster 700 - Shuang Ni; Jingwen Wang; Danni Lyu; Zhe Xu; Jing-Wei Xu; Sha Zhu; Yixuan Feng; Ce Shi; Wen Xu (Scientific Reports)
Abstract This study aimed to evaluate the accuracy of six intraocular lens (IOL) calculation formulas using total keratometry (TK) and standard keratometry (K) measurements from the IOLMaster 700 in various ocular subgroups. A total of 212 eyes were analyzed. The mean absolute error (MAE), standard deviation (SD) of prediction error, and the median absolute error (MedAE) were calculated for each formula. and the prediction accuracy was compared across different subgroups categorized by axial length (AL), anterior chamber depth (ACD), lens thickness (LT), and other ocular parameters. Results showed that the Barrett Universal II (BU II) formula consistently had the lowest MAEs and MedAEs in the overall sample and most subgroups. The BU II formula performed particularly well in subgroups with thin LT when using TK mode and in medium LT subgroups using K mode. Comparison between TK and K modes showed no consistent superiority, with each mode outperforming the other in specific subgroups. The accuracy of the BU II formula was not influenced by ocular parameters, suggesting its robustness across different patient groups. In conclusion, the BU II formula demonstrated superior accuracy compared to other formulas, especially in specific subgroups, and its performance remained consistent regardless of ocular measurement variations.